2022
DOI: 10.18632/aging.204209
|View full text |Cite
|
Sign up to set email alerts
|

A signature constructed with mitophagy-related genes to predict the prognosis and therapy response for breast cancer

Abstract: Over the past decades, the incidence and mortality rates of breast cancer (BC) have increased rapidly; however, molecular biomarkers that can reliably detect BC are yet to be discovered. Our study aimed to identify a novel signature that can predict the prognosis of patients with BC. Data from the TCGA-BRCA cohort were analyzed using univariate Cox regression analysis, and least absolute shrinkage and selection operator (LASSO) analysis was performed to build a stable prognostic model. Subsequently, Kaplan-Mei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Mitophagy as a selective degradation process, is critical to keeping mitochondria healthy, producing ATP, and maintaining neuronal activity and survival by removing impaired mitochondria. MRGs have been previously reported as prognostic or diagnostic markers for various tumors, including pancreatic cancer ( Zhuo et al, 2022 ), breast cancer ( Zhao et al, 2022 ), and liver cancer ( Chen et al, 2021 ; Xu et al, 2022 ), whereas only a limited number of studies have examined the usefulness of them as AD biomarkers. Pakpian et al (2020) recently reported that alterations in mitochondrial dynamic-related genes in the peripheral blood may be useful for diagnosing AD.…”
Section: Discussionmentioning
confidence: 99%
“…Mitophagy as a selective degradation process, is critical to keeping mitochondria healthy, producing ATP, and maintaining neuronal activity and survival by removing impaired mitochondria. MRGs have been previously reported as prognostic or diagnostic markers for various tumors, including pancreatic cancer ( Zhuo et al, 2022 ), breast cancer ( Zhao et al, 2022 ), and liver cancer ( Chen et al, 2021 ; Xu et al, 2022 ), whereas only a limited number of studies have examined the usefulness of them as AD biomarkers. Pakpian et al (2020) recently reported that alterations in mitochondrial dynamic-related genes in the peripheral blood may be useful for diagnosing AD.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, predicting a patient's prognosis in PDAC using these markers is challenging. Additionally, in the early diagnosis of PDAC, the detection of single tumor markers, such as CEA, CA199, and CA125, is difficult to reach the ideal level of sensitivity and specificity (21)(22)(23)(24)(25)(26) which could anticipate the OS duration of PDAC patients (27). As per the expression of immune-related genes such as MMP14 and INHBA, Xu et al developed a predictive risk model to assess PADC patients' prognoses and identify PDAC therapy opportunities (28).…”
Section: Discussionmentioning
confidence: 99%
“…A univariate Cox regression analysis was conducted to determine DEGs associated with prognosis. Then, using multivariate Cox and least absolute shrinkage and selection operator (LASSO) regression analyses by "caret", "glmnet" and "survival" packages, thress genes were selected and integrated into the prognostic signature (15). The median risk score was used to classify individuals with PDAC into two categories (low-and high-risk categories).…”
Section: Development and Verification Of The Urgs Prognostic Signaturementioning
confidence: 99%
“…eg. db" and "DOSE" to conduct gene ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment (9,10).…”
Section: Differential Expression Of Genes Screening Weighted Correlat...mentioning
confidence: 99%